Differential Effector Response of Amnion‐ and Adipose‐Derived Mesenchymal Stem Cells to Inflammation; Implications for Intradiscal Therapy. Issue 11 (25th July 2019) - Borem, Ryan; Madeline, Allison; Bowman, Mackenzie; Gill, Sanjitpal; Tokish, John; Mercuri, Jeremy
ABSTRACT: Intervertebral disc degeneration (IVDD) is a progressive condition marked by tissue destruction and inflammation. The therapeutic effector functions of mesenchymal stem cells (MSCs) makes them an attractive therapy for patients with IVDD. While several sources of MSCs exist, the optimal choice for use in the inflamed IVD remains a significant question. Adipose (AD)‐ and amnion (AM)‐derived MSCs have several advantages compared with other sources, however, no study has directly compared the impact of IVDD inflammation on their effector functions. Human MSCs were cultured in media with or without supplementation of interleukin‐1β (IL‐1β) and tumor necrosis factor‐α at concentrations reportedly produced by IVDD cells. MSC proliferation and production of pro‐ and anti‐inflammatory cytokines were quantified following 24 and 48 h of culture. Additionally, the osteogenic and chondrogenic potential of AD‐ and AM‐MSCs was characterized via histology and biochemical analysis following 28 days of culture. In inflammatory culture, AM‐MSCs produced significantly more anti‐inflammatory IL‐10 (14.47 ± 2.39 pg/ml; p = 0.004) and larger chondrogenic pellets (5.67 ± 0.26 mm 2 ; p = 0.04) with greater percent area staining positively for glycosaminoglycan (82.03 ± 3.26%; p < 0.001) compared with AD‐MSCs (0.00 ± 0.00 pg/ml; 2.76 ± 0.18 mm 2 ; 34.75 ± 2.49%; respectively). Conversely, AD‐MSCs proliferated more resulting in higher cell numbers (221, 000 ± 8, 021 cells; p = 0.048) and produced higher concentrations of pro‐inflammatory cytokines prostaglandin E2 (1, 118.30 ± 115.56 pg/ml; p = 0.030) and IL‐1β (185.40 ± 7.63 pg/ml; p = 0.010) compared with AM‐MSCs (109, 667 ± 5, 696 cells; 1, 291.40 ± 78.47 pg/ml; 144.10 ± 4.57 pg/ml; respectively). AD‐MSCs produced more mineralized extracellular matrix (3.34 ± 0.05 relative absorbance units [RAU]; p < 0.001) compared with AM‐MSCs (1.08 ± 0.06 RAU). Under identical inflammatory conditions, a different effector response was observed with AM‐MSCs producing more anti‐inflammatories and demonstrating enhanced chondrogenesis compared with AD‐MSCs, which produced more pro‐inflammatory cytokines and demonstrated enhanced osteogenesis. These findings may begin to help inform researchers which MSC source may be optimal for IVD regeneration. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:2445–2456, 2019